Peningkatan Higher Order Thinking Skills dengan Pembelajaran Berbasis Masalah - Ervina; Jackson Pasini Mairing; Yumiati (JURNAL PENDIDIKAN, 2022)
Higher Order Thinking Skills (HOTS) or higher order thinking skills are demands of today's curriculum. However, the facts at SMPN 2 Kapuas Tengah Satu Roof show that students at the school do not yet have this ability. This study is intended to describe the effect of problem-based learning on HOTS. His research uses a quantitative approach with a quasi-experimental type. The population is junior high school students in Kapuas Tengah District, Kapuas Regency. The samples were class VII A and VIII A (experimental class), and class VII B and VIII B (control class). The instruments are pre-test and post-test. Data were analyzed using N-gain and covariate analysis. The conclusion shows that the increase in HOTS from pre-test to post-test as measured using N-gain in students who learn with problem-based lea[1]rning is better than those who learn using conventional learning. Problem-based learning has an effect on HOTS which is indicated by the HOTS of students in problem-based learning classes more than students in conventional learning classes.